A Transdiagnostic Perspective on Youth Irritability. (October 2021) - Klein, Daniel N.; Dougherty, Lea R.; Kessel, Ellen M.; Silver, Jamilah; Carlson, Gabrielle A.
Irritability is increasingly recognized as a significant clinical problem in youth. It is a criterion for multiple diagnoses and predicts the development of a wide range of disorders. Research on its etiology suggests that genetic and family environmental factors play a role, as do abnormalities in reward and cognitive-control neural circuitry. However, many of these effects are age dependent. Threat-responsive self-regulatory systems and the degree to which irritability is tonic or phasic influence whether irritable youth exhibit more internalizing or more externalizing outcomes.